Superelongation of Liquid Metal. Issue 11 (7th February 2022) - Li, Xiangpeng; Cao, Lu; Xiao, Bing; Li, Fangxia; Yang, Junhui; Hu, Jie; Cole, Tim; Zhang, Yuxin; Zhang, Mingkui; Zheng, Jiahao; Zhang, Shiwu; Li, Weihua; et al.
Abstract: The ability to control interfacial tension electrochemically is uniquely available for liquid metals (LMs), in particular gallium‐based LM alloys. This imparts them with excellent locomotion and deformation capabilities and enables diverse applications. However, electrochemical oxidation of LM is a highly dynamic process, which often induces Marangoni instabilities that make it almost impossible to elongate LM and manipulate its morphology directly and precisely on a 2D plane without the assistance of other patterning methods. To overcome these limitations, this study investigates the use of an LM–iron (Fe) particle mixture that is capable of suppressing instabilities during the electrochemical oxidation process, thereby allowing for superelongation of the LM core of the mixture to form a thin wire that is tens of times of its original length. More importantly, the elongated LM core can be manipulated freely on a 2D plane to form complex patterns. Eliminating Marangoni instabilities also allows for the effective spreading and filling of the LM–Fe mixture into molds with complex structures and small features. Harnessing these excellent abilities, a channel‐less patterning method for fabricating elastomeric wearable sensors is demonstrated to detect motions. This study shows the potential for developing functional and flexible structures of LM with superior performance. Abstract : Tuning interfacial tension is an effective way to manipulate fluids at small scales. This study investigates the liquid metal–iron particle mixture that can suppress surface Marangoni instabilities, thereby allowing for superelongation of the liquid metal core electrically in an electrolyte to form a thin wire. The elongated core can be manipulated freely on a 2D plane to form complex patterns.